Retrospective Analysis of Therapeutic Drug Monitoring Data for Treatment of Bipolar Disorder with Lamotrigine - Unholzer, S.; Haen, E. (Pharmacopsychiatry, 2015)
Introduction: Lamotrigine is licensed for treatment of epilepsy and prevention or at least delay of depressive episodes in bipolar disorder. The accepted therapeutic reference range (TRR) of lamotrigine for anticonvulsant treatment is 3 000–14 000 ng/ml. This TRR is often used for the therapy of bipolar disorders as well. This work presents serious doubts about this approach.Methods: KONBEST, a large TDM database containing patients’ characteristics including diagnoses, doses, comedication and serum concentrations, was analyzed. Out of a total of 3 459 lamotrigine samples, 360 patients suffered from bipolar disorder. 82 of them benefitted from therapy with lamotrigine as judged by the clinical global impression of improvement (CGI-I) scale. Patients with a score of minimally (3), much (2) or very much improved (1) were considered as responders.Results: The recommended lamotrigine maintenance dose for bipolar disorder is 200 mg/day; the doses prescribed in our samples ranged from 25 to 450 mg/day. Only 32 concentrations (39.0%) fitted into the TRR recommended for therapy of epilepsy; 50 (61.0%) did not reach it, none exceeded it. The lowest concentration was 177 ng/ml, the highest 11 871 ng/ml. A mean lamotrigine serum concentration of 3 341±2 563 ng/ml (̅x±SD) was detected in the patients who benefitted.Discussion: The authors conclude that in bipolar disorder lower lamotrigine serum concentrations lead to therapeutic benefit.
Keywords: lamotrigine; bipolar disorder; mood stabilizer; TDM; therapeutic reference range